FRI0005 Combination Blocking of IL-22 and IL-17 During Experimental Arthritis Potently Reduces TH17-Driven Disease Progression. (9th June 2015) - Roeleveld, D.M.; Rogier, R.; Walgreen, B.; Helsen, M.M.; van den Bersselaar, L.; van den Berg, W.B.; van der Kraan, P.M.; Koenders, M.I.
Abstract : Background: Rheumatoid arthritis (RA) patients show elevated levels of IL-22 and IL-22-producing T helper cells that correlate to erosive disease, suggesting a role for this cytokine in the pathogenesis of RA. Interestingly, IL-22 is a dual cytokine with pro- and anti-inflammatory properties, and its effects might be regulated by cooperation and crosstalk with IL-17. Objectives: The purpose of this study was to elucidate the role of IL-22 in the development of a spontaneous model of experimental arthritis by using IL-1Ra knockout mice. Additionally, we aimed to investigate the therapeutic potential of combined IL-22/IL-17 blocking during experimental arthritis. Methods: IL-1Ra-deficient mice develop spontaneous arthritis due to excess IL-1 signaling, and we previously demonstrated the importance of IL-17 and Th17 cells in this model 1 . To investigate the role of IL-22 in this arthritis model, we compared IL-1Ra -/- x IL-22 +/+ mice to IL-1Ra -/- mice lacking IL-22 expression. Paw joint swelling was scored weekly, and mice were sacrificed at the age of fifteen weeks. In addition, arthritic IL-1Ra -/- x IL-22 -/- mice were treated with anti-IL-17 antibodies to determine the therapeutic potency of this combined blocking strategy during experimental arthritis. Results: IL-1Ra -/- mice that also lack IL-22 showed strongly reduced arthritis development, reaching a disease incidence of only 54% at the age of 15 weeks compared to 93% in IL-1Ra -/- x IL-22 +/+ mice. In addition, arthritis severity of the mice that did develop arthritis was significantly reduced by 30.6% in the absence of IL-22. Interestingly, combined blocking of IL-22 and IL-17 using IL-1Ra -/- x IL-22 -/- mice treated with neutralizing anti-IL-17 antibodies after the onset of arthritis demonstrated clear additive effects compared to blocking these single cytokines alone, thereby potently reducing progression of this Th17-driven arthritis model. Conclusions: These findings suggest that IL-22 plays an important role both in the initiation and augmentation of Th17-dependent experimental arthritis, and that targeting IL-22, especially in combination with IL-17 therefore seems an interesting, potent strategy in RA treatment. References: Koenders MI, Devesa I, Marijnissen RJ, Abdollahi-Roodsaz S, Boots AM, Walgreen B, di Padova FE, Nicklin MJ, Joosten LA, van den Berg WB. Interleukin-1 drives pathogenic Th17 cells during spontaneous arthritis in interleuking-1 receptor antagonist-deficient mice. Arthritis Rheum. 58(11): 3461-70, 2008. Disclosure of Interest: None declared